Another brother - Cordell, Matthew 1975- (New York : Feiwel and Friends, 2012)
Davy the sheep wishes he had time alone with his parents, as he did before his twelve brothers came along and started imitating his every move, but when his wish comes true Davy misses playing with the youngsters.
Accelerated Reader
Reading Counts!
Accelerated Reader AR
A Junior Library Guild selection
107069
Keywords: Brothers -- Juvenile fiction; Imitation -- Juvenile fiction; Families -- Juvenile fiction; Sheep -- Juvenile fiction; Picture books for children; Picture books; Fiction; Juvenile works